مها ا رت تقديم الب ا رمج الإذاعية و علاقتها بإستقطاب المستمعين - رقية مشراوي; حورية عيداوي; /د-مداني حجاج (جامعة عمار ثليجي الاغواط, 2023)
الملخص: هدفت د ا رستنا الى الكشف عن حجم اهتمام الاذاعة المحلية بمها ا رت تقديم الب ا رمج الاذاعية والتعرف عن طريقة بث الب ا رمج الاذاعية في الاذاعة المحليةّ،معرفة علاقة مها ا رت تقديم الب ا رمج الاذاعية باستقطاب المستمعين ، حيث توصلت الد ا رسة الى النتائج التالية التي نذكر أهمها : اهتمام كلا الجنسيين بالإذاعة وب ا رمجها التي تساهم في توعية كل حسب مجاله . إهتمام أغلب المستمعين ذلك لأن معظم ب ا رمج الإذاعة تتمحور حول مواضيع تهمهم وهذا هو الذي يدفعها لمتابعة ب ا رمج الإذاعة عكس الفئات الاخرى التي تبقى الإذاعة بالنسبة لهم كوسيلة كمالية لانشغالاتهم بأمور الحياة. - يلعب المستوى التعليمي دو ا ر كبي ا ر في الإستماع الى الإذاعة حيث لاحظنا أن إ رتفاع نسبة الشباب الجامعيين يرجع الى إهتمامهم بالإذاعة كوسيلة تعليمية و ثقافية عكس المستويات الأخرى التي نرى أنه ليس لهاعلاقة كبيرة بالإذاعة . -للإذاعة دور بارز في حياة المجتمع من خلال تسليطها الضوء على جميع مجالات الحياة ولها دور كبير في تنمية الوعي الإجتماعي فهي تستمد ب ا رمجها من المجتمع وهذا يظهر في تقييمهم الجيد لها . -تلعب الإذاعة دو ا ر كبي ا ر في تشكيل وجدان المستمع من خلال إشباع حاجته للمعرفة التي يحتاجها و تنمية مجاله المعرفي وثقافته العامة , وامداده بالنوع الذي يفضله من باقة الب ا رمج التي تقدمها عبر أثيرها . -كلما كانت اللغة مناسبة في طرح المواضيع كلما ازداد عدد المستمعين لها . يفضل المستمع ون للإذاعة اللهجة العامية الدارجة لأنها اللهجة الأقرب إليهم فهم يستمتعون حين يخاطبهم المذيع باللهجة الخاصة لكل منطقة كما أنه يوجد مستمعون لايفقهون اللغة الفصحى وبذلك يصعب عليهم ويتعسر فهم معظم ألفاظها. الكلمات المفتاحية: الإذاعة المحلية، مها ا رت تقديم الب ا رمج، استقطاب المستمعين. Abstract : Two studies aimed to reveal the extent of the local radio's interest in the skills of presenting radio programs and to identify the method of broadcasting radio programs on the local radio, to know the relationship of the skills of presenting radio programs to attracting listeners. The interest of both nationalities in radio and its programs that contribute to educating each according to his field. The interest of most of the listeners is because most of the radio programs revolve around topics of interest to them, and this is what drives them to follow the radio programs, unlike other groups for whom radio remains as a means of luxury for their preoccupations with life matters. - The educational level plays a major role in listening to the radio, as we noticed that the high percentage of university youth is due to their interest in radio as an educational and cultural means, unlike other levels that we see that it has little to do with radio. - Radio has a prominent role in the life of society by shedding light on all areas of life and has a great role in developing social awareness, as it derives its programs from society and this appears in their good evaluation of it. Radio plays a major role in shaping the conscience of the listener by satisfying his need for the knowledge he needs, developing his field of knowledge and general culture, and providing him with the type he prefers from the package of programs that it offers through its broadcasts. The more appropriate the language in presenting the topics, the greater the number of listeners to it. Radio listeners prefer the colloquial dialect because it is the closest dialect to them. They enjoy when the broadcaster addresses them in the special dialect of each region. There are also listeners who do not understand the classical language, and thus it is difficult for them and difficult to understand most of its words. Keywords: Local radio / Radio presenting skills / Attracting listeners
د ا رسة ميدانية على عينة من مستمعيي إذاعة الأغواط المحلية